INTERNAL STRATEGIES AND MECHANISMS FOR COMBATING CORRUPTION DURING THE COVID-19 PANDEMIC IN ZAMBIA: A LINGUISTIC TURN - Chidongo, Phiri (Journal of Anti-Corruption Law, 2023)
This article analyses internal strategies and mechanisms in Zambia that have triggered corruption challenges during the Covid-19 pandemic. In doing so, it focuses on a localised practice known as the bineyi phenomenon and adopts John Law’s actor network theory (ANT) as an analytical prism. Bineyi is a colloquial word in Nyanja which refers to favours in exchange for funds from individuals and government officials. Simply, Bineyi entails a system of business social networking in which influential businesspeople seek to gain favours. These social systems are dimensions and units of actions of individuals, and their roles as plausible human activities. ANT, in turn, is a social science approach which assumes networks of social relations and structures that are dynamic.